The Holocaust in the East: Local Perpetrators and Soviet ResponsesMichael David-Fox, Peter Holquist, and Alexander M. Martin - Zavadivker, Polly (Holocaust and genocide studies, 2017)
The nine essays under review cohere and productively engage one another in confronting major problems and questions in the fields of Soviet, East European, and Holocaust studies, including the collaboration of local populations and the USSR’s ambiguous attempts to document, publicize, and prosecute the crimes, and to commemorate the victims., Five of the essays appeared previously in the journal Kritika: Explorations in Russian and Eurasian History, while essays by Tarik Cyril Amar, Diana Dumitru, and Zvi Gitelman, along with an introduction by John-Paul Himka, appear for the first time.